EFEKTIFITAS YOGURT TERHADAP pH SALIVA ANAK USIA 8-9 TAHUN PADA SISWA/I SD NEGERI 067247 MEDAN TUNTUNGAN - SIMAREMARE, ASNITA BUNGARIA; Angela; Irma Syafriani Sinaga (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2026)
Oral and dental health is significantly influenced by salivary pH balance, which can be affected by food and beverage consumption. Yogurt is known as a probiotic food that can improve the balance of microflora in the oral cavity and maintain optimal salivary pH. This study aims to describe the effect of yogurt consumption on salivary pH in 8–9-years old at State Elementary School 067247 Medan Tuntungan. This study used direct oral examination of the respondents. The respondents in this study were 30 students at State Elementary School 067247 Medan Tuntungan. Salivary pH measurements were conducted before and after consuming 240 ml plain yogurt by using pH strip saliva. The results showed an increase in the average salivary pH from acidic (5.97) to neutral (6.5) after yogurt consumption. Before consumption, 36.7% of students had an alkaline pH, 33.3% had a normal pH, and 30% had an acidic pH; after consumption, the normal saliva pH increased to 63.34%. These results indicate that consuming yogurt can neutralize salivary pH. The conclusion of this study is that yogurt consumption can help maintain salivary pH balance and potentially support children's dental and oral health.